Field-Programmable Gate Array-Based Chaos Oscillator Implementation for Analog–Discrete and Discrete–Analog Chaotic Synchronization Applications - Ruslans Babajans; Darja Cirjulina; Deniss Kolosovs (Entropy)
This work focuses on evaluating the behavior of analog chaos oscillators in field-programmable gate arrays (FPGAs). This work is motivated by a new approach to designing chaos-based communication systems using chaos oscillator circuits implemented in hardware in the transmitter and the mathematical models of the oscillator implemented on an FPGA in the receiver. Such a hybrid approach opens new possibilities for chaos-based modulation schemes for wireless sensor network (WSN) applications. This work brings a hybrid chaos-based communication system closer to realization by implementing the chaos oscillators on an FPGA and achieving analog–discrete and discrete–analog chaotic synchronization. First, this paper derives a model that simulates the dynamics of Vilnius and RC chaos oscillators using Euler–Cromer numerical integration in fixed-point arithmetic. The derived MATLAB model precisely describes the digital design and is thus directly transferred to VHDL. The synthesized digital design is compiled onto an FPGA chip and is then used to achieve analog–discrete and discrete–analog Pecora–Carroll chaotic synchronization.